Pelatihan Desain Media Edukatif dalam Pemahaman Stunting Bagi Guru PAUD - Roni Priyanda; Munawir Munawir; Nishbah Fadhelina (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
The problem of stunting is not only the responsibility of the government and the health department, but it is also our shared responsibility, especially in universities, through the Tridharma of University it is hoped that it can provide action in reducing stunting, several actions that can be taken include; provide and ensure access to clean water and sanitation, provide education and care for parents and students, provide good education for early childhood, and take a persuasive approach to families at risk of stunting. Stunting cases must be addressed immediately by conducting a convergence of stunting reduction among the targets, namely; early childhood, adolescents and parents, the method that can be done is to educate the public about stunting, how to avoid it and how to overcome it, which is targeted in community service based on the results of an initial analysis of the understanding of stunting, namely PAUD IT Bismillah and PAUD Nurul Fikrih, then dissemination is carried out about stunting how to prevent and treat it, then given training on how to design educational media so that teachers can find out more information about stunting, and summarize it in a poster, after the teacher is an expert in making posters then the teacher is taught how to make twibon, this is useful so that the target who became the locus of stunting knew more, by participating in preventing stunting.